Edukasi Cara Sikat Gigi Pada Ibu Siswa TK Perwanida Kotawaringin Barat Kalimantan Tengah - Shesanthi Citrariana; Tri Megawati (FKIP, Universitas Palangka Raya, 2023)
Dental health is part of overall health. Mother's level of knowledge has an important role in maintaining dental health in her child. Preschoolers are children aged between 4-6 years which is called the